Genetic Improvement of Sweet Potato: Influence of Selection Method in Early Stages of the Programme - de Oliveira, Darllan Junior Luiz Santos Ferreira [UNESP]; Toledo, Geissiane Neves [UNESP]; Pavan, Bruno Ettore [UNESP]; Vargas, Pablo Forlan [UNESP] (Wiley, 2025)
Plant breeding programmes: every stage of the process is crucial for the ultimate success. Currently, for sweet potato cultivation, the primary selection methods used in the initial stage of the genetic improvement programme are based on selection indices, techniques that require significant labour and time. Given this, the aim of this study was to estimate genetic parameters and compare different initial selection methods, namely, the traditional method using the selection rank index and a newly proposed methodology using visual analysis. The study comprised three experiments. The studies were conducted in an area belonging to the Faculty of Agrarian and Veterinary Sciences (FCAV) on the Jaboticabal Campus, located in the municipality of Jaboticabal, SP, Brazil. The first involved selection of the initial population conducted in summer (August–December 2021), using a randomized complete block design with two replications, evaluating 512 treatments (510 genotypes and two cultivars). Subsequent experiments in summer (December 2021–April 2022) and winter (April–September) evaluated 30 genotypes selected in the first cycle and one cultivar (Beauregard) using a randomized complete block design with three replications. Harvesting in the summer experiments occurred 120 days after planting, while in winter, it occurred at 150 days. Statistical analyses were performed on the data. The highest heritabilities were found for commercial root yield (PC) (0.69) and flesh colour (CP) (0.79). Regarding direct selection gain, the predicted gains were significant, ranging from −21.21% to 119.58%, indicating a favourable condition for selection. The estimated selection gains were higher than those achieved for PC alone. However, for general shape (FG), commercial pattern (PDC) and flesh colour (CP), the actual gains exceeded the estimated ones. The realized heritability was lower than the estimated one for commercial root yield (PC) but higher for general shape (FG), commercial pattern (PDC) and flesh colour (CP), except for commercial pattern (PDC) in winter cultivation using the index and flesh colour (CP) in summer cultivation using the visual method. In conclusion, the visual selection method is deemed viable for the initial stage of sweet potato genetic improvement.
Keywords: Ipomoea batatas L; Mulamba and Mock; selection index; visual selection